Two-component polyurethane composite adhesive and preparation method thereof

Through cashew phenol-modified carbon nanotubes and grafted aminophenylthiophenol, the mechanical properties of polyurethane composite adhesives are improved, the problems of plasticizer migration and environmental hazards are solved, and a denser network structure is formed, which significantly improves the composite materials. mechanical properties.

CN118440656BActive Publication Date: 2024-12-31CHANGYING NEW MATERIAL (YANTAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410579627.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2024-12-31
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

Commonly used plasticizers such as phthalates in existing polyurethane adhesives are potentially harmful to human health and the environment, and migrate to the surface of the product during processing and use, affecting the mechanical properties, and are low intoxication and natural plasticization. The problem of the migration of agents under thermodynamic reasons remains to be solved.

Method used

By using cashew phenol to modify carbon nanotubes and grafted aminothiophenol, the dispersion and compatibility of carbon nanotubes are improved, the mechanical properties of the composite materials are enhanced, and cashew phenol is prevented through non-polar long chain and benzene ring structure. Migrate, preventing contact between water vapor and -NCO groups.

Benefits of technology

It significantly improves the mechanical properties of the composite material, forms a denser network structure, improves the cross-linking density of the polyurethane system, prevents the migration of cashew phenol, and enhances the mechanical properties during the curing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000006982520000021
    Figure GHA0000006982520000021
  • Figure GHA0000006982520000041
    Figure GHA0000006982520000041
  • Figure GHA0000006982520000051
    Figure GHA0000006982520000051
Patent Text Reader

Abstract

The present invention relates to a two-component polyurethane composite adhesive and a preparation method thereof, and belongs to the technical field of adhesives. A two-component polyurethane composite adhesive comprises component A and component B, wherein component A comprises polytetramethylene ether polyol, filler, composite modified carbon nanotube, catalyst, leveling agent, coupling agent and antioxidant; component B comprises MDI and HDI; the preparation method comprises the steps of: mixing the raw materials of component A, cooling, vacuum discharging and packaging; mixing the raw materials of component B uniformly at 60-70°C, and vacuum discharging and packaging. The present invention improves the dispersibility and compatibility of carbon nanotubes and fillers by modifying carbon nanotubes by cardanol and aminothiophenol, thereby significantly improving the mechanical properties of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives and relates to a two-component polyurethane composite adhesive and a preparation method thereof. Background Art

[0002] Two-component solvent-free polyurethane adhesive is an adhesive that does not contain any solvent and consists of only two components, A and B. Component A is mainly composed of terminal hydroxyl groups of polyols, and component B is a polyurethane prepolymer terminated with -NCO. Additives can be selectively added to component A or component B. During use, components A and B are mixed evenly in an appropriate proportion and applied to the surface of the adherend. Subsequently, the hydroxyl groups on the polyol react with the isocyanate groups on the isocyanate to crosslink, thereby achieving curing and making the adherends tightly bonded.

[0003] In order to improve the toughness and processing properties of polyurethane adhesives, plasticizers are usually added during the processing. The addition of plasticizers can significantly enhance the flexibility and fluidity of polyurethane adhesives. Commonly used plasticizers include tri-n-butyl acetyl citrate and phthalates, such as dioctyl phthalate, dibutyl phthalate, etc. As a physical plasticizer, tri-n-butyl acetyl citrate does not participate in the system reaction, is free in the coating, and reduces the mechanical properties of the coating. On the one hand, phthalate plasticizers pose potential hazards to human health and the environment; on the other hand, due to their poor compatibility with macromolecules, they will gradually migrate to the surface of the product during processing and use. Therefore, this type of plasticizer is restricted in certain fields. Low-toxic natural plasticizers have gradually become a research hotspot, including epoxidized soybean oil, fatty acid esters, sunflower seed oil, cardanol, etc. However, due to thermodynamic reasons, the migration problem of plasticizers in polymer products remains to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a two-component polyurethane composite adhesive and a preparation method thereof. The present invention modifies carbon nanotubes by cardanol and aminothiophenol to improve the dispersibility and compatibility of carbon nanotubes and fillers, thereby significantly improving the mechanical properties of the composite material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A two-component polyurethane composite adhesive comprises a component A and a component B in a mass ratio of 1:1.

[0007] Component A includes the following components by weight:

[0008]

[0009] Component B includes the following components by weight:

[0010] MDI 65-75 parts

[0011] HDI 30-34 parts.

[0012] As a preferred technical solution of the present invention, the method for preparing the composite modified carbon nanotubes comprises the following steps:

[0013] 1) After ultrasonically mixing carboxylated carbon nanotubes, isopropanol and cardanol, adding a catalyst, heating and stirring under an inert atmosphere, filtering, washing, and vacuum drying to obtain cardanol-modified carbon nanotubes;

[0014] 2) After the cardanol-modified carbon nanotubes and isopropanol are stirred and mixed, aminothiophenol and a photoinitiator are added, and the mixture is stirred and mixed under ultraviolet irradiation, filtered, washed, and vacuum dried to obtain composite modified carbon nanotubes.

[0015] As a preferred technical solution of the present invention, carboxylated carbon nanotubes are prepared: carbon nanotubes are added to an acid solution and heated at 60°C for mixing, condensed and refluxed for 4 hours in an ultrasonic cleaner with an ultrasonic power of 200W and an ultrasonic frequency of 40KHz, diluted with deionized water, and then filtered with a microporous filter membrane with a diameter of 0.2μm, repeatedly washed with deionized water until neutral, and finally baked at 80°C for 12 hours, ground into powder, and carboxylated carbon nanotubes are obtained; wherein the amount ratio of the acid solution to the carbon nanotubes is 100mL:0.5g.

[0016] As a preferred technical solution of the present invention, in step 1), the ultrasonic mixing is at 300-400W and 30-45min; the heating stirring is at 100-110°C and 400-600r / min and 2-3h; the vacuum drying temperature is 85°C; and the inert atmosphere is a nitrogen atmosphere.

[0017] As a preferred technical solution of the present invention, in step 1), the mass ratio of the carboxylated carbon nanotubes to isopropanol is 1-1.2:5.

[0018] As a preferred technical solution of the present invention, in step 2), the photoinitiator is photoinitiator 1173; the wavelength of the ultraviolet irradiation is 365-400nm; and the stirring and mixing time is 5-6h.

[0019] As a preferred technical solution of the present invention, in step 2), the mass ratio of the cardanol-modified carbon nanotubes to isopropanol is 1:8; the mass ratio of the aminothiophenol to the photoinitiator is 2.5-2.8:0.14.

[0020] As a preferred technical solution of the present invention, the mass ratio of the carboxylated carbon nanotubes, cardanol, catalyst and aminothiophenol is 15-16: 5-6: 0.26-0.30: 2-3.

[0021] As a preferred technical solution of the present invention, the catalyst is one or two of p-toluenesulfonic acid and trifluoroacetic acid; the aminothiophenol is 3-aminothiophenol.

[0022] As a preferred technical solution of the present invention, the molecular weight of the polytetramethylene ether polyol is 1500-2000; the leveling agent is one or two of polydimethylsiloxane and polymethylalkylsiloxane; the antioxidant is one or two of p-phenylenediamine and diaryl secondary amine; the catalyst is dibutyltin diacetate; and the silica is TS-720 purchased from Cabot Corporation.

[0023] As a preferred technical solution of the present invention, the filler is a mixture of calcium carbonate, zinc oxide and silicon dioxide in a mass ratio of 2-2.5:1-1.3:5-6; the coupling agent is one or more of the silane coupling agents KH-560, KH-550, KH-570, KH-792 and DL602.

[0024] The present invention discloses a method for preparing the above-mentioned two-component polyurethane composite adhesive, the preparation method comprising the following steps:

[0025] Component A: Mix the raw materials of component A at 30-50℃ for 60 minutes, cool, and vacuum discharge and package;

[0026] Component B: Mix the raw materials of component B evenly at 60-70℃, and then vacuum discharge and package.

[0027] Beneficial effects of the present invention:

[0028] 1. The present invention improves the dispersibility of carbon nanotubes in a polyurethane system by modifying carbon nanotubes with cardanol, while enhancing the compatibility between the filler and the polyurethane system and improving the mechanical properties of the composite material.

[0029] 2. The present invention grafts aminothiophenol so that the composite modified carbon nanotubes have both -OH and -NH2, which react with the -NCO group to introduce a large number of rigid benzene rings, significantly improve the crosslinking density of the polyurethane system, and form a denser network structure.

[0030] 3. The present invention can prevent the migration of cardanol through the non-polar long chain and benzene ring structure, and prevent water vapor from contacting the -NCO group during the curing process, thereby further improving the mechanical properties. DETAILED DESCRIPTION

[0031] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0032] Example 1

[0033] A two-component polyurethane composite adhesive comprises a component A and a component B in a mass ratio of 1:1.

[0034] Component A includes the following components by weight:

[0035]

[0036]

[0037] Component B includes the following components by weight:

[0038] MDI 65 parts

[0039] HDI 30 parts;

[0040] The molecular weight of the polytetrahydrofuran ether polyol is 1500;

[0041] The leveling agent is polydimethylsiloxane;

[0042] The antioxidant is p-phenylenediamine;

[0043] The catalyst is dibutyltin diacetate;

[0044] The coupling agent is silane coupling agent KH-560;

[0045] The filler is prepared by mixing calcium carbonate, zinc oxide and silicon dioxide in a mass ratio of 2:1:5;

[0046] The preparation method of the composite modified carbon nanotubes comprises the following steps:

[0047] 1) After ultrasonically mixing carboxylated carbon nanotubes, isopropanol and cardanol, adding a catalyst, heating and stirring under an inert atmosphere, filtering, washing, and vacuum drying to obtain cardanol-modified carbon nanotubes;

[0048] In step 1), the ultrasonic mixing is performed at 300W for 30 minutes; the heating stirring is performed at 100°C and 400r / min for 2 hours; the vacuum drying temperature is 85°C; and the inert atmosphere is a nitrogen atmosphere;

[0049] In step 1), the mass ratio of the carboxylated carbon nanotubes to isopropanol is 1:5;

[0050] 2) stirring and mixing the cardanol-modified carbon nanotubes and isopropanol, adding aminothiophenol and a photoinitiator, stirring and mixing under ultraviolet irradiation, filtering, washing, and vacuum drying to obtain composite modified carbon nanotubes;

[0051] In step 2), the photoinitiator is photoinitiator 1173; the wavelength of the ultraviolet irradiation is 365 nm; the stirring and mixing time is 5 h;

[0052] In step 2), the mass ratio of the cardanol-modified carbon nanotubes to isopropanol is 1:8; the mass ratio of the aminothiophenol to the photoinitiator is 2.5:0.14;

[0053] In the preparation of the composite modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, cardanol, catalyst and aminothiophenol is 15:5:0.26:2; the catalyst is p-toluenesulfonic acid; and the aminothiophenol is 3-aminothiophenol.

[0054] A method for preparing a two-component polyurethane composite adhesive, the preparation method comprising the following steps:

[0055] Component A: Mix the raw materials of component A at 30°C for 60 minutes, cool, and vacuum discharge and package;

[0056] Component B: Mix all the raw materials of component B at 60℃ and then vacuum discharge and package.

[0057] Example 2

[0058] A two-component polyurethane composite adhesive comprises a component A and a component B in a mass ratio of 1:1.

[0059] Component A includes the following components by weight:

[0060]

[0061] Component B includes the following components by weight:

[0062] MDI 70 parts

[0063] HDI 32 parts;

[0064] The molecular weight of the polytetrahydrofuran ether polyol is 1750;

[0065] The leveling agent is polydimethylsiloxane;

[0066] The antioxidant is p-phenylenediamine;

[0067] The catalyst is dibutyltin diacetate;

[0068] The coupling agent is silane coupling agent KH-560;

[0069] The filler is made of calcium carbonate, zinc oxide and silicon dioxide in a mass ratio of 2.2:1.2:5.5;

[0070] The preparation method of the composite modified carbon nanotubes comprises the following steps:

[0071] 1) After ultrasonically mixing carboxylated carbon nanotubes, isopropanol and cardanol, adding a catalyst, heating and stirring under an inert atmosphere, filtering, washing, and vacuum drying to obtain cardanol-modified carbon nanotubes;

[0072] In step 1), the ultrasonic mixing is performed at 350W for 38 minutes; the heating and stirring is performed at 105°C and 500r / min for 2.5 hours; the vacuum drying temperature is 85°C; and the inert atmosphere is a nitrogen atmosphere;

[0073] In step 1), the mass ratio of the carboxylated carbon nanotubes to isopropanol is 1.1:5;

[0074] 2) stirring and mixing the cardanol-modified carbon nanotubes and isopropanol, adding aminothiophenol and a photoinitiator, stirring and mixing under ultraviolet irradiation, filtering, washing, and vacuum drying to obtain composite modified carbon nanotubes;

[0075] In step 2), the photoinitiator is photoinitiator 1173; the wavelength of the ultraviolet irradiation is 382 nm; the stirring and mixing time is 5.5 h;

[0076] In step 2), the mass ratio of the cardanol-modified carbon nanotubes to isopropanol is 1:8; the mass ratio of the aminothiophenol to the photoinitiator is 2.6:0.14;

[0077] In the preparation of the composite modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, cardanol, catalyst and aminothiophenol is 15.5:5.5:0.28:2.5; the catalyst is p-toluenesulfonic acid; and the aminothiophenol is 3-aminothiophenol.

[0078] A method for preparing a two-component polyurethane composite adhesive, the preparation method comprising the following steps:

[0079] Component A: Mix the raw materials of component A at 40°C for 60 minutes, cool, and vacuum discharge and package;

[0080] Component B: Mix all the raw materials of component B at 65℃ and then vacuum discharge and package.

[0081] Example 3

[0082] A two-component polyurethane composite adhesive comprises a component A and a component B in a mass ratio of 1:1.

[0083] Component A includes the following components by weight:

[0084]

[0085] Component B includes the following components by weight:

[0086] MDI 75 parts

[0087] HDI 34 parts;

[0088] The molecular weight of the polytetrahydrofuran ether polyol is 2000;

[0089] The leveling agent is polydimethylsiloxane;

[0090] The antioxidant is p-phenylenediamine;

[0091] The catalyst is dibutyltin diacetate;

[0092] The coupling agent is silane coupling agent KH-560;

[0093] The filler is a mixture of calcium carbonate, zinc oxide and silicon dioxide in a mass ratio of 2.5:1.3:6;

[0094] The preparation method of the composite modified carbon nanotubes comprises the following steps:

[0095] 1) After ultrasonically mixing carboxylated carbon nanotubes, isopropanol and cardanol, adding a catalyst, heating and stirring under an inert atmosphere, filtering, washing, and vacuum drying to obtain cardanol-modified carbon nanotubes;

[0096] In step 1), the ultrasonic mixing is performed at 400W for 45 minutes; the heating stirring is performed at 110°C and 600r / min for 3 hours; the vacuum drying temperature is 85°C; and the inert atmosphere is a nitrogen atmosphere;

[0097] In step 1), the mass ratio of the carboxylated carbon nanotubes to isopropanol is 1.2:5;

[0098] 2) stirring and mixing the cardanol-modified carbon nanotubes and isopropanol, adding aminothiophenol and a photoinitiator, stirring and mixing under ultraviolet irradiation, filtering, washing, and vacuum drying to obtain composite modified carbon nanotubes;

[0099] In step 2), the photoinitiator is photoinitiator 1173; the wavelength of the ultraviolet irradiation is 400 nm; the stirring and mixing time is 6 hours;

[0100] In step 2), the mass ratio of the cardanol-modified carbon nanotubes to isopropanol is 1:8; the mass ratio of the aminothiophenol to the photoinitiator is 2.8:0.14;

[0101] In the preparation of the composite modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, cardanol, catalyst and aminothiophenol is 16:6:0.30:3; the catalyst is p-toluenesulfonic acid; and the aminothiophenol is 3-aminothiophenol.

[0102] A method for preparing a two-component polyurethane composite adhesive, the preparation method comprising the following steps:

[0103] Component A: Mix the raw materials of component A at 50°C for 60 minutes, cool, and vacuum discharge and package;

[0104] Component B: Mix the raw materials of component B evenly at 70°C, and then vacuum discharge and package.

[0105] Comparative Example 1

[0106] Compared with Example 2, the difference in Comparative Example 1 is that carbon nanotubes replace carboxylated carbon nanotubes, and the other components, preparation steps and parameters are the same.

[0107] Comparative Example 2

[0108] Compared with Example 2, Comparative Example 2 is different in that step 1);

[0109] Step 1) After ultrasonically mixing isopropanol and cardanol, a catalyst is added and heated and stirred under an inert atmosphere, followed by filtering, washing, vacuum drying, and adding carboxylated carbon nanotubes to mix to obtain cardanol-modified carbon nanotubes;

[0110] The remaining components, preparation steps and parameters were the same.

[0111] Comparative Example 3

[0112] Compared with Example 2, Comparative Example 3 is different in that thiophenol is used instead of aminothiophenol, and the other components, preparation steps and parameters are the same.

[0113] Comparative Example 4

[0114] Compared with Example 2, Comparative Example 4 is different in that aminothiophenol is not used, and the remaining components, preparation steps and parameters are the same.

[0115] Comparative Example 5

[0116] Compared with Example 2, the difference in Comparative Example 5 is that the heating and stirring in step 1) is at 105° C., 500 r / min, and stirring for 1 hour, and the other components, preparation steps and parameters are the same.

[0117] The components A and B obtained in Examples 1-3 and Comparative Examples 1-5 were mixed and cured to obtain finished products and the following tests were performed:

[0118] Mechanical properties test: According to GB / T528-2009, the test results are shown in Table 1.

[0119] Table 1

[0120] Tensile strength(MPa) Elongation at break (%) Example 1 35.3 458 Example 2 35.6 463 Example 3 35.1 456 Comparative Example 1 27.4 408 Comparative Example 2 29.2 434 Comparative Example 3 28.2 419 Comparative Example 4 25.7 383 Comparative Example 5 27.1 405

[0121] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the tensile strength and elongation at break of the adhesive obtained in Examples 1-3 of the present invention after curing are significantly better than those in Comparative Examples 1-5. This is because the carboxylated carbon nanotubes contain more active sites, which are conducive to the entry of cardanol into the interlayer of the carbon nanotubes, and then the cardanol undergoes a self-polymerization reaction on the carboxylated carbon nanotubes to form a dense network structure, which improves the dispersibility of the carbon nanotubes in the polyurethane system, and can also play a role in increasing the volume between the filler and the polyurethane system, thereby improving the mechanical properties of the composite material. Then, by grafting aminothiophenol, the composite modified carbon nanotubes are provided with -OH and -NH2 at the same time, which can react with -NCO groups, and a large number of rigid benzene rings are introduced to significantly improve the crosslinking density of the polyurethane system, so that it forms a more dense network structure; at the same time, the presence of non-polar long chains and benzene ring structures reduces the migration of cardanol, while effectively preventing water vapor from contacting with -NCO groups during the curing process, further improving its mechanical properties.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A two-component polyurethane composite adhesive, characterized in that: It includes component A and component B in a mass ratio of 1:

1. Component A includes the following components by weight: 90-100 parts of polytetramethylene ether polyol Filler 10-13 parts 5-6 parts of composite modified carbon nanotubes Catalyst 2.0-2.5 parts 2-4 parts of leveling agent Coupling agent 1.5-1.8 parts 1-2 parts of antioxidants; Component B includes the following components by weight: MDI 65-75 parts HDI 30-34 parts; The molecular weight of the polytetramethylene ether polyol is 1500-2000; the leveling agent is one or two of polydimethylsiloxane and polymethyl alkylsiloxane; the antioxidant is one or two of p-phenylenediamine and diaryl secondary amine; the catalyst is dibutyltin diacetate; the filler is a mixture of calcium carbonate, zinc oxide and silicon dioxide in a mass ratio of 2-2.5:1-1.3:5-6; the coupling agent is one or more of silane coupling agents KH-560, KH-550, KH-570, KH-792 and DL602; The preparation method of the composite modified carbon nanotubes comprises the following steps: 1) After ultrasonically mixing carboxylated carbon nanotubes, isopropanol and cardanol, a catalyst is added and heated and stirred under an inert atmosphere, followed by filtering, washing and vacuum drying to obtain cardanol-modified carbon nanotubes; the mass ratio of the carboxylated carbon nanotubes to isopropanol is 1-1.2:5; the ultrasonic mixing is performed at 300-400W for 30-45min; the heating and stirring is performed at 100-110°C and 400-600r / min for 2-3h; the vacuum drying temperature is 85°C; and the inert atmosphere is a nitrogen atmosphere; 2) After mixing the cardanol-modified carbon nanotubes and isopropanol, adding aminothiophenol and a photoinitiator, mixing under ultraviolet irradiation, filtering, washing, and vacuum drying to obtain composite modified carbon nanotubes; the mass ratio of the cardanol-modified carbon nanotubes to the isopropanol is 1:8; the mass ratio of the aminothiophenol to the photoinitiator is 2.5-2.8:0.14; In the preparation of the composite modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, cardanol, catalyst and aminothiophenol is 15-16: 5-6: 0.26-0.30: 2-3.

2. A two-component polyurethane composite adhesive according to claim 1, characterized in that: In step 2), the photoinitiator is photoinitiator 1173; the wavelength of the ultraviolet irradiation is 365-400 nm; and the stirring and mixing time is 5-6 h.

3. A two-component polyurethane composite adhesive according to claim 1, characterized in that: The catalyst is one or two of p-toluenesulfonic acid and trifluoroacetic acid; the aminothiophenol is 3-aminothiophenol.

4. A method for preparing a two-component polyurethane composite adhesive as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Component A: Mix the raw materials of component A at 30-50℃ for 60 minutes, cool, and vacuum discharge and package; Component B: Mix the raw materials of component B evenly at 60-70℃, and then vacuum discharge and package.